Comparison of the effects of a colloidal solution of cadmium telluride quantum dots and cadmium ions on the proliferative activity of Allium cepa L. root meristems - Lakhturov, A.S.; Smirnov, O.E.; Kovalenko, M.S.; Kapush, O.А.; Dzhagan, V.M.; Schwartau, V.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
The effect of a solution of quantum dots based on cadmium telluride (CdTe QD) as a powerful cytostatic effector was investigated, by using a standard Allium-test system. The cytostatic effects of the experimental CdTe QD solution at the organismal level were manifested in a decrease in the linear growth and biomass of Allium cepa L. roots, while, at the level of root cells, the proliferative activity was recorded. The effect of the investigated CdTe QD solution at the concentration of 10 μM was compared with the effects caused by a 10 μM CdI2 solution. The multi-vector nature of cytogenetic breaches has been established. It was shown that the use of CdTe QD solution in the studied concentration as a substrate significantly inhibited root growth and proliferative activity of meristematic cells, inhibiting mitosis without obvious clastogenic and aneugenic effects. The use of 10 μM CdI2 solution as a substrate led to an increase in the frequency of clastogenic pathologies of mitosis by 24 %.